PENGARUH MODEL NUMBERED HEAD TOGETHER DENGAN PERMAINAN INDEX CARD MATCH TERHADAP HASIL BELAJAR KELAS III - Muhammad Agus Wartono; Khusnul Fajriyah; Ibnu Fatkhu Royana (JURNAL SINEKTIK, 2020)
The purpose of this research is to find out the influence of the application of Numbered Head Together model assisted by Index Card Match media to improve learning outcomes in thematic learning of sub-theme material 1 “ Growth and Development of Living Things SD N 01 Sumbersari. The research design used is One-Group Pretest-Posttest Design. The results stated that there is an influence of NHT learning model with Index Card Match game on learning result on the theme material 1 “Growth and Development of Living Things” SD N 01 Sumbersari village Ngampel District Kendal district with the acquisition of tcount 5.667, then tcount 5.667> ttable1.699,